Methods for Producing Heat-Resistant Oligomers - Sirgiyevich, Rosilov Mansur; o‘g‘li, Qodirov Alibek Rauf (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Despite the attractiveness of this approach in the creation of polymer parts and assemblies for structural purposes, the use of laser stereolithography is currently limited to the creation of prototypes and models of various products and assemblies.